Pelayanan Kegiatan Keagamaan Bagi Masyarakat Kecil Melalui Pelayanan Nilai-Nilai Keagamaan di Masa Pandemik di Sulawesi Barat - Ramadhan, Farida Aulia; Sachbana, Ihza; Sarmila, Dina; Ramadhan, Rizal; Lestari, Sustika; Zubaydah, Sirli; Azzahrani, Della; Huda, Miftahul; Ilhamsyah, Nur Syaban (TAFANI: Jurnal Pengabdian Masyarakat, 2022)
The learning carried out aims to improve cooperation and learning outcomes for class IV students at MI Nahdatul Wathon Tenggarong Seberang through the application of the Think Pair Share type cooperative learning model. The learning results show that after implementing the Think Pair Share type cooperative learning model in the Aqidah Akhlak subject, cooperation and student learning outcomes have increased.